GALLERI ARSITEKTUR BANJAR - Saifudin, Febry Ramadan; Mentayani, Ira (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Banjar Architecture Gallery is one of the solutions to increase the interest of the people of Banjarmasin city for the benefit of developing their own city. The essence needed about building construction can be a creative and educative socialization agent to make visitors understand Banjarmasin city architecture. In the end, the Architectural Gallery Design can be realized as a single mass building by presenting a Banjar house holographic collection presented from the house, the history of the house's hierarchy, and the initial process of making a house. On the 1st floor tells the history and process of making banjarise house. The second floor is where we proceed with hologram technology.